A pillar-layered porous CoII-MOF with dual active sites for selective gas adsorption. Issue 34 (17th August 2018) - Gao, Xiang; Zhang, Shan-Shan; Yan, Hui; Li, Yun-Wu; Liu, Qing-Yun; Wang, Xing-Po; Tung, Chen-Ho; Ma, Hui-Yan; Sun, Di
Abstract : A pillar-layered microporous MOF has been constructed from linear trimeric {Co3 (COO)6 } clusters as SBUs. It exhibits preferential selective uptake of C2 H2 /C2 H4, C2 H2 /C2 H6 and CO2 /N2 owing to its dual active sites. Abstract : A pillar-layered microporous MOF (SD/Co3) has been constructed from trimeric {Co3 (COO)6 } clusters as SBUs and mixed ligands as linkers. It exhibits preferential selective adsorption of C2 H2 /C2 H4, C2 H2 /C2 H6 and CO2 /N2, owing to its dual active sites including uncoordinated nitrogen sites from pyrimidine groups and unsaturated metal centres (UMCs) exposed in channels.